Addressing Global Challenges - Exploring Socio-Cultural Dynamics and Sustainable Solutions in a Changing World: Proceedings of International Symposium on Humanities and Social Sciences (ISHSS 2023, August 11-13, 2023, Macau, China) (Taylor & Francis, 2025)
The International Symposium on Humanities and Social Sciences: Addressing Global Challenges-Exploring Socio-Cultural Dynamics and Sustainable Solutions in a Changing World (ISHSS 2023) unfolds as a crucial academic undertaking, centred around the overarching theme of intellectual synergy and inquiry. This conference serves as a vibrant forum, facilitating discussions on a wide array of subjects within the realms of humanities and social sciences. The curated collection of proceedings encapsulates an expansive spectrum of subject areas, transcending disciplinary boundaries to encapsulate sociology, anthropology, history, and beyond. The significance of this compilation lies not only in the wealth of knowledge it imparts but also in its potential to resonate with a diverse audience. From academicians to practitioners, the discourse transcends traditional boundaries, offering insights that cater to the intellectual curiosity of a broad audience. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.